Finite element modelling of powder compaction process - Rajalingam Manimaran (2008)
Cold compaction of metal powders is widely used in the industry. The ability to produce the required shape and dimensions of a component with very little or without subsequent machining is the main advantage compared to other production processes. The manufacture of a powder compacted component may roughly be split up in two steps. First the powder is compacted to desired shape and subsequently the compact is sintered in order to weld the powder particles together and thereby attain the desired strength. Focus in the present work will be on cold die compaction where plastic deformation of the powder particles is the major deformation process. At higher temperatures, diffusion and creep start to play a role.